Comparative evaluation of antibacterial property and substantivity of chlorhexidine containing dentifrices with sodium lauryl sulfate and Tween as surfactants: An in vivo study - V Venu; A R Prabhakar; N Basappa (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of the study was to determine the antibacterial property and substantivity of chlorhexidine containing dentifrices with sodium lauryl sulfate (SLS) and Tween as surfactants. Materials and Methods: It is a double-blind cross over the study, a total of 20 children within their mixed dentition period (7-13 year) having Streptococci mutans count more than 10 6 were selected for the main study. Three types of chlorhexidine containing dentifrices were used with a washout period of 1 week. Out of the three toothpastes, one was without surfactant and other two toothpastes contained SLS and Tween as surfactants respectively. 20 volunteers brushed for 1 min during the study day with their assigned toothpaste. Saliva samples were collected before brushing, immediately after brushing and 1, 3, 5, and 7 hand sent for microbial analysis. The culture carried out by inoculating saliva sample onto Mitis salivarius agar for selective isolation of S. mutans followed by counting of colony forming unit. Results: Group I and III (Chlorhexidine and CHX + Tween) had shown statistically significant reduction in bacterial count until 7 h when compared to their baseline values ( P < 0.001). Group II toothpaste (CHX + SLS) had shown significant reduction in bacterial count until 3 h only. On inter group comparison, Group III had shown good amount of percentage reduction in bacterial count when compared to other groups. Conclusion: CHX + Tween toothpaste had shown statistically significant reduction in antibacterial activity and substantivity than other groups. These findings show chlorhexidine containing toothpaste with non-ionic surfactant will be able to maintain the antibacterial property and substantivity of chlorhexidine.